Large‐scale disturbance legacies and the climate sensitivity of primary Picea abies forests. (16th February 2018) - Schurman, Jonathan S.; Trotsiuk, Volodymyr; Bače, Radek; Čada, Vojtěch; Fraver, Shawn; Janda, Pavel; Kulakowski, Dominik; Labusova, Jana; Mikoláš, Martin; Nagel, Thomas A.; Seidl, Rupert; Synek, Michal; et al.
Abstract: Determining the drivers of shifting forest disturbance rates remains a pressing global change issue. Large‐scale forest dynamics are commonly assumed to be climate driven, but appropriately scaled disturbance histories are rarely available to assess how disturbance legacies alter subsequent disturbance rates and the climate sensitivity of disturbance. We compiled multiple tree ring‐based disturbance histories from primary Picea abies forest fragments distributed throughout five European landscapes spanning the Bohemian Forest and the Carpathian Mountains. The regional chronology includes 11, 595 tree cores, with ring dates spanning the years 1750–2000, collected from 560 inventory plots in 37 stands distributed across a 1, 000 km geographic gradient, amounting to the largest disturbance chronology yet constructed in Europe. Decadal disturbance rates varied significantly through time and declined after 1920, resulting in widespread increases in canopy tree age. Approximately 75% of current canopy area recruited prior to 1900. Long‐term disturbance patterns were compared to an historical drought reconstruction, and further linked to spatial variation in stand structure and contemporary disturbance patterns derived from LANDSAT imagery. Historically, decadal Palmer drought severity index minima corresponded to higher rates of canopy removal. The severity of contemporary disturbances increased with each stand's estimated time since last major disturbance, increased with mean diameter, and declined with increasing within‐stand structural variability. Reconstructed spatial patterns suggest that high small‐scale structural variability has historically acted to reduce large‐scale susceptibility and climate sensitivity of disturbance. Reduced disturbance rates since 1920, a potential legacy of high 19th century disturbance rates, have contributed to a recent region‐wide increase in disturbance susceptibility. Increasingly common high‐severity disturbances throughout primary Picea forests of Central Europe should be reinterpreted in light of both legacy effects (resulting in increased susceptibility) and climate change (resulting in increased exposure to extreme events). Abstract : Climate change has been linked to increasing forest disturbance rates and large‐scale disturbance histories are needed to assess how disturbance legacies modulate climate–disturbance dynamics. Historical disturbance rates (c. 1750–2000), reconstructed with tree cores collected from primary Picea abies forests throughout Central‐Eastern Europe, have exhibited moderate sensitivity to drought extremes; developmental feedbacks are important determinants of a forest's responsiveness to climate‐induced events. Widespread increases in forest age have occurred throughout the 20th century and these developmental patterns, in addition to climate change, are responsible for the severity of recent disturbances.